Eternal Iran : continuity and chaos - Clawson, Patrick, 1951- (Middle East in focus series., 2005)
From pillar of stability to rogue state, Iran's politics have been a centre of world attention and concern. With a glorious history as an empire, ethnically diverse population, and youthful inhabitants, the country has and will continue to play a critical role as a pivotal state in the Middle East, Central Asia and the Caucasus. Oil wealth mixes with extensive poverty to explain the strength of the state and the potential for unrest in a country that experienced two revolutions in the twentieth century. Exploring continuities and changes, this book provides the historical backdrop crucial to understanding how Iranian pride and sense of victimization combine to make its politics contentious and potentially dangerous. From the struggle between the Shah and Ayatollah Khomeini to the current tension between the reformers and traditionalists, a central issue in Iranian domestic politics has long been its place in the world and relations with the West.